Seasonal Distribution of Trace Metals in Ground and Surface Water of Golaghat District, Assam, India - M. Boarh; A. K. Misra (E-Journal of Chemistry)
A study has been carried out on the quality of ground and surface water with respect to chromium, manganese, zinc, copper, nickel, cadmium and arsenic contamination from 28 different sources in the predominantly rural Golaghat district of Assam (India). The metals were analysed by using atomic absorption spectrometer. Water samples were collected from groundwater and surface water during the dry and wet seasons of 2008 from the different sources in 28 locations (samples). The results are discussed in the light of possible health hazards from the metals in relation to their maximum permissible limits. The study shows the quality of ground and surface water in a sizeable number of water samples in the district not to be fully satisfactory with respect to presence of the metals beyond permissible limits of WHO. The metal concentration of groundwater in the district follows the trend As>Zn>Mn>Cr>Cu>Ni>Cd in both the seasons.